The Effect of Titanium Oxide Substrate on the Film Morphology and Photoluminescence Properties of Organometal Halide Perovskites. Issue 1771 (2015) - Xu, Zhihua; Chen, Zhengtao
ABSTRACT: We have investigated the film morphology and photoluminescence properties of spin-coated CH3 NH3 PbI3-x Clx films on mesoporous and compact TiO2 substrates. We observe that the perovskite film deposited on the mesoporous substrate composed of 20 nm TiO2 nanopaticles exhibits relatively uniform grain size, while the films deposited on the compact TiO2 substrate and the mesoporous substrate with large TiO2 nanoparticles (200 nm) show highly heterogeneous film morphology. The heterogeneity of film morphology has significant effect on the photoluminescence spectra and lifetime of the perovskite films. The result of time-resolved confocal microscopy unveils the relation between film structure and photoluminescence properties.